Badania nad metodami powstawania i działalności przestępczości zorganizowanej w Stanach Zjednoczonych Ameryki Północnej w piśmiennictwie polskim przełomu XIX i XX wieku - Antonów, Radosław (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
Organized crime in the United States emerged at the turn of the twentieth century as a result of a clash between American and European elements. In great urban agglomerations, the first colonizers, their descendants, and immigrants from European countries created competing, dynamically developing, and ruthless criminal organizations, or gangs, which primarily took control over illegal practices connected with prostitution, gambling, and the trade in alcohol. In order to strengthen and protect their position, in addition to violence, criminals resorted to cultivating corrupt politicians and individuals who held public offices. Through the use of democratic methods they also exerted influence over elections for political and self-government positions, as well as public offices. In the initial decades of the twentieth century, organized crime in the US took the form of connections between criminal activity on the one hand, and political and economic activity on the other.
Keywords: przestępczość; przestępczość zorganizowana; Stany Zjednoczone Ameryki Północnej; gangi; gangsteryzm; bezpieczeństwo narodowe; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa narodowego i międzynarodowego; terroryzm kryminalny